PD-1 inhibitors plus anti-angiogenic therapy with or without intensity-modulated radiotherapy for advanced hepatocellular carcinoma: A propensity score matching study - Su, Ke; Guo, Lu; Ma, Wenqiong; Wang, Jing; Xie, Yunchuan; Rao, Mingyue; Zhang, Jianwen; Li, Xueting; Wen, Lianbin; Li, Bo; Yang, Xiaoli; Song, Yanqiong; et al. (Frontiers in Immunology, 2022)
Background Whether intensity-modulated radiotherapy (IMRT) can enhance the efficacy of the programmed death 1 (PD-1) inhibitors combined with anti-angiogenic therapy for hepatocellular carcinoma (HCC) is unclear. Therefore, we conducted this multicenter retrospective study to investigate the efficacy of the combination of PD-1 inhibitors with anti-angiogenic therapy and IMRT. Methods From April 2019 to March 2022, a total of 197 patients with HCC [combination of PD-1 inhibitors and anti-angiogenic therapy and IMRT (triple therapy group), 54; PD-1 inhibitors + anti-angiogenic therapy (control group), 143] were included in our study. Propensity score matching (PSM) was applied to identify two groups with similar baselines. The objective response rate (ORR), overall survival (OS), and progression-free survival (PFS) of the two groups were compared before and after matching. Results Prior to PSM, the triple therapy group had higher ORR (42.6% vs 24.5%, P = 0.013) and more superior median OS (mOS) (20.1 vs 13.3 months, P = 0.009) and median PFS (mPFS) (8.7 vs 5.4 months, P = 0.001) than the control group. Following PSM, the triple therapy group still exhibited better mPFS (8.7 vs 5.4 months, P = 0.013) and mOS (18.5 vs 12.6 months, P = 0.043) than the control group. However, the ORR of two groups was similar (40% vs 25%, P = 0.152). No significant difference was observed in the treatment-related 48 adverse events between the two groups (P < 0.05 for all). Conclusions The combination of PD-1 inhibitors with anti-angiogenic therapy and IMRT for HCC is a promising regimen.